THE IMPLEMENTATION OF EXTENSIVE READING TO FOSTER STUDENTS’ READING SKILL - Diska Fatima Virgiyanti; Andi Nur Fadhila Mahdiyah (Journal of Research on Language Education, 2023)
This paper aims to review some previous studies and theories related to the effect of extensive reading to boost students’ reading ability. Moreover, good reading ability is an important skill that should be mastered by students. It is used to enhance students’ knowledge and reading ability. However, students facing several difficulties in upgrading their reading skill, such as limited time to read, uninteresting reading materials given in the classroom, and unsupportive reading environment. Thus, this condition made students to have low reading ability. Extensive reading is chosen as a method to overcome students’ reading problems and difficulties. It is implemented by asking students to read as much as possible what they like outside the classroom. The purpose of this activity is to create supportive reading atmosphere for students. Furthermore, this paper will describe students’ difficulties in reading, the definition of extensive reading, and the advantages of implementing extensive reading in teaching reading. Extensive reading is also proven by some experts as an effective method to assist students reading challenges.